2002
DOI: 10.1002/jrs.893
|View full text |Cite
|
Sign up to set email alerts
|

A Raman study of the lithium insertion process in vanadium pentoxide thin films deposited by atomic layer deposition

Abstract: Micro-Raman spectrometry was applied to the characterization of the Li x V 2 O 5 phases (0 ≤ x ≤ 1.8) electrochemically produced from V 2 O 5 thin films prepared by atomic layer deposition (ALD). An electrochemical study showed that V 2 O 5 ALD films constitute attractive positive electrodes for rechargeable lithium microbatteries. The good homogeneity and crystallinity of the films allowed us to obtain highresolution Raman spectra and to follow their transformation as lithium insertion proceeds. Specific Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 36 publications
11
115
1
1
Order By: Relevance
“…Knoops et al reported the deposition of planar and 3D fi lms of TiN and TaN, which may serve as lithium diffusion barrier layers, [ 224 , 229 , 230 ] and 3D layers of platinum that can be used as cathode current collector. [ 231 , 232 ] Also the deposition of active electrode materials like V 2 O 5 , [ 233 ] Another, more common technique to deposit low vapor pressure materials is sputter deposition. In this case the target is bombarded by high energy ions, either created by a plasma above the target or by an ion-gun.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…Knoops et al reported the deposition of planar and 3D fi lms of TiN and TaN, which may serve as lithium diffusion barrier layers, [ 224 , 229 , 230 ] and 3D layers of platinum that can be used as cathode current collector. [ 231 , 232 ] Also the deposition of active electrode materials like V 2 O 5 , [ 233 ] Another, more common technique to deposit low vapor pressure materials is sputter deposition. In this case the target is bombarded by high energy ions, either created by a plasma above the target or by an ion-gun.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…It has been recently and successfully applied to follow the structural changes occurring in a Li x V 2 O 5 thinfilm electrode. [28,32,34] In this paper, a detailed description of the structural modifications induced in a Li x V 2 O 5 composite cathode during lithium electrochemical intercalation in the 4-2.15 V potential range is provided for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…V 2 O 5 films obtained by the ALD method have been shown to act as performant alkali ion storage material with electrochemical applications mostly in the area of Li microbatteries and of electrochromic windows. 3,4 Films less than 100 nm thick have the additional advantage that they usually adhere very well to the substrate, and equilibrium of the intercalant ion (usually Li or Na) inside the oxide host can be reached in a very short time, is the order of a few seconds for an ion with diffusion coefficient of 10 11 cm 2 s 1 .…”
Section: Introductionmentioning
confidence: 99%